An efficient approach for integration of sensor resources into the grid. (23rd November 2011) - Li, Chunlin; Li, LaYuan
Grid computing paradigm can be extended to include the sharing of sensor resources in sensor network. Sensor enabled grid may combine real time data about physical environment with vast computational resources derived from the grid architecture. One of the major challenges in the design of sensor enabled grid is how to efficiently schedule sensor resource to user jobs across the collection of sensor resources in a sensor grid. The paper studies optimal sensor resources allocation in sensor enabled grid computing environment. The paper presents an efficient mechanism to assign sensor resources to appropriate sensor grid users on the basis of negotiation results among participants. We model sensor allocation problem by introducing the sensor utility function. The goal is to find a sensor resource allocation that maximises the total profit. The paper proposes a distributed optimal sensor resource allocation algorithm. The performance evaluation of proposed algorithm is evaluated and compared with other resource allocation algorithm for sensor grid. The paper also gives the application example of proposed approach.